DESCRIPTIVE ANALYSIS OF KUR PROGRAM FOR UMKM DEVELOPMENT IN POJOK VILLAGE, NGANTRU DISTRICT, TULUNGAGUNG REGENCY - Puspitasari, Intan (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
Research on the effectiveness of loan capital management on the development of MSME businesses was conducted in Pojok Village, Ngantru District, Tulungagung Regency, precisely at CV Pupuk Cair Semoga Jaya. This study aims to analyze the effectiveness of the financing program channeled through BRI Bank to CV Pupuk Cair Semoga Jaya using a descriptive qualitative approach method. This approach describes the problem systematically and factually regarding the phenomenon of the BRI KUR financing scheme. Research data were obtained based on interviews with BRI officers, sub-district heads, and MSME business actors at CV Pupuk Cair Semoga Jaya. The results, based on the researcher's analysis, the target of the KUR program is right on target. Meanwhile, the amount of money lent is adjusted to the scale of the business and the customer's ability to pay installments. In terms of the timeliness of distribution, it is based on the business cycle because the principle of BRI KUR is to meet production and business needs. In terms of the accuracy of installment burdens, the KUR officers and BRI Bank always conduct careful credit analysis so that the amount of installments does not burden customers. While the last aspect is that the loan procedure can be fully understood by the borrower with the help of the local credit officer.